Overview of the Mother's Level of Knowledge About Dental and Oral Health In Toddlers at Paud Al Barokah - Risma Putri Sabrina; Ade Nuraeni; Nuridha Fauziyah (Jurnal Medika Nusantara, 2025)
Dental and oral health is a key indicator of overall health, well-being and quality of life. Knowledge of children's dental health is a must for a mother for the development of children. The purpose of this study is to provide an overview of mothers' level of knowledge about dental and oral health. This study is a type of quantitative research with a cross-sectional research design. The sample in the study was 30 people with a total sampling technique. Data collection uses a questionnaire on the level of maternal knowledge; data analysis uses frequency distribution. The study's results showed that the characteristics of age were mostly in the early adult category of 70.0%, non-working work as much as 73.4%, high school education level as much as 50.0%, and most mothers have a high level of knowledge as much as 73.0%. Good knowledge will encourage mothers to always improve their children's dental and oral health. This research can be used as information to maintain dental and oral health.